Adsorption of aromatics on the (111) surface of PtM and PtM3 (M = Fe, Ni) alloys1. Issue 104 (11th November 2015) - Hensley, Alyssa J. R.; Schneider, Sebastian; Wang, Yong; McEwen, Jean-Sabin
<x xml:space="preserve">Abstract</x> Tuning the Pt/M ratio tailors the adsorption characteristics of aromatics, similar to Pd/Fe systems, with applications for hydrodeoxygenation catalysis.